Relationship of heart rate variability with iron status in metabolic syndrome - Munni, Halima Akter; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2020)
Background: Clustering of some most dreadful cardiovascular risk factors gives rise to metabolic syndrome (MetS). Higher iron status and impaired cardiac autonomic status may important play role in increased risk of cardiovascular morbidity in this group of patients. Objective: To observe the relationship of HRV with iron status in patients with MetS. Methods: This cross-sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from March, 2019 to February, 2020. For this study, 35 MetS female patients aged 25 to 45 years were enrolled in MetS group and equal number of age and sex matched apparently healthy subjects constituted control group. For evaluation of iron status, serum iron, serum ferritin, total iron binding capacity (TIBC) and transferrin saturation (Tsat) were measured by autoanalyzer. HRV was assessed by Powerlab 8/35, AD instruments, Australia. Data were expressed as mean±SD. Statistical analysis was done by Independent sample ‘t’ test and Pearson’s correlation coefficient test as applicable. Results: In this study, resting pulse rate, systolic blood pressure (SBP), diastolic blood pressure (DBP) were significantly (p<0.001) higher and mean heart rate, standard deviation of the RR intervals (SDRR),mean R-R interval, standard deviation of the difference betweensuccessive RR intervals (SDSD), square root of mean squared differences of successive RR intervals (RMSSD), proportion of difference of successive RR interval greater than 50 ms (pRR50) were significantly (p<0.001) lower in MetS patients compared to control. Among the parameters of iron status, serum ferritin was significantly (p£<0.05) higher and TIBCwas significantly(p<0.05) lower in MetS patients in comparison to control. On correlation analysis, only the TIBC showed significant positive correlation with mean RR interval, SDRR, CVRR, SDSD, RMSSD, pRR50 (p<0.05) in MetS patients. Conclusion: This study reveals that poor parasympathetic activity is related to higher iron status in metabolic syndrome patients. J Bangladesh Soc Physiol. 2020, June; 15(1): 46-53